Public health, racism and dentistry: Analysis of the treatment of the black prison population in the Unified Health System (Research, Society and Development, 2021)
There is a problem or an increase in the incarcerated population and the consequences related to social inequality for institutions that develop social policies as a way to improve living conditions in prison. In relation to health conditions, or the State, in the last thirty years, it created three specific policies for the prison population: the Penal Enforcement Law (LEP), or National Health Plan in the Penitentiary System (PNSSP) and the National Policy for Comprehensive Care to the Health of Persons Deprived of Liberty in the Prison System (PNAISP). Thus, the objective of the project in question is to carry out the analysis of health policies, correlating them with the quality of life that the black prison population has from studies on the population's systemic and oral health. We conclude that, according to the social context in which the black population is inserted, these factors can influence oral and systemic health in the same way. It is important that there is specific health care for the black population, as it is a more fragile population, being subject to various crises such as diabetes mellitus, tuberculosis, sickle cell anemia, among others. In addition, we can observe that it does not imprison the black population and the majority in unhealthy health conditions, weakening a large part of this population. There is an urgent need to implement health care for the black population, based on two health professionals, so that the population's oral, systemic and mental health can be acquired, ensuring direct attention to the health of individuals.